A simple protocol for the production of commercial-grade Taq DNA polymerase and its “hot start” version at laboratory scale - Nam, Vu Tuan; Chom-Kyu, Chong; Dung, Le Tien (Academia Journal of Biology, 2015)
PCR (Polymerase Chain Reaction) is a versatile molecular biology technique which uses DNA polymerase to amplify target DNA fragments. Taq ADN polymerase, a thermostable DNA polymerase originally isolated from the thermophilic bacterium Thermus aquaticus, is frequently used in PCR and DNA sequencing. The objective of this study was to test a simplified, but reliable, procedure for the expression and purification of recombinant Taq DNA polymerase from E. coli and development of its “hotstart” version. Our results showed that a protocol consists of heat treatment, ammonium sulfate precipitation and dialysis steps were sufficient to produce commercial-grade Taq ADN polymerase. For every batch of 0.5 L culture medium, we obtained 2.0-2.5 mL of purified Taq DNA polymerase roughly equivalent to 7,000-8,000 units of commercial Taq DNA polymerase, which value about US1,500 of imported similar product. By the addition of 100 ng of specific antibody against Taq ADN polymerase per unit of the isolated enzyme, we could produce the “hotstart” version which affectively inhibited non-specific amplification in PCR reactions. The enzyme produced in this study was shown to be compatible with various types of PCR template, including genomic DNA, plasmid DNA and cDNA. Taken together, our data showed that this simple protocol can be applied to express and purify Taq ADN polymerase enzyme that is qualified for research use in molecular biology laboratories.